Measuring the effects of Bitcoin forks on selected cryptocurrencies using event study methodology - Tomić, Nenad (Industrija, 2020)
Cryptocurrencies have been at the center of interest of both academic and professional community for over a decade. Due to the highly volatile exchange rate against convertible currencies, investors use cryptocurrencies as an instrument of speculative investment, while their use in payments are negligible. Over the last few years, all leading cryptocurrencies have recorded highly volatile rates of return, which have often had a negative value. The paper uses the event study methodology to determine the statistical significance of the abnormal return of leading cryptocurrencies after the three Bitcoin forks. The forks were viewed as three isolated events, with the estimations windows and the event windows constructed separately for each of them. There were statistically significant negative effects during the second and third event, related to the creation of Bitcoin Gold and Bitcoin SV. Contrary to the expectations, in the case of the first and most famous Bitcoin fork, which created the Bitcoin Cash, there was no statistically significant effect
Keywords: Bitcoin, forks, event study, cryptocurrencies